Pengaruh Strategi Marketing Mix Terhadap Volume Penjualan Produk Blackmores pada PT. Enseval Putera Megatrading Tbk - Nadeak, Lukas Haruman; Sabrina, Hesti (Universitas Medan Area, 2025)
This study aims to determine that an effective marketing mix strategy can increase consumer appeal. Expand the market and ultimately encourage increased sales volume. This study is a type of causal associative research with a quantitative approach with a population in this study amounting to 3,191 customers, then using the slovin formula, the number of samples was determined as 100 customers whose sampling criteria were determined based on the purposive sampling technique, namely customers who have made more than 2 Blackmores Product purchase transactions at PT. Enseval Putera Megatrading Tbk. Data collection was carried out by directly distributing questionnaires so that the data obtained was processed using SPSS. Based on the results of the study, partially the product has a positive and significant effect on sales volume, partially the price has a positive and significant effect on sales volume, partially the location does not affect sales volume, partially the promotion has a positive and significant effect on sales volume, while simultaneously the product, price, location, and promotion have a positive and significant effect on sales volume.